Early Repair of Anterior and Distal Hypospadias is less Cmplicable than Delayed Repair (Journal of Shaheed Suhrawardy Medical College, 2017)
Background: Evaluation of the result of early and delayed repair of anterior and distal penile hypospadias. A total number of 144 patients of anterior and distal penile hypospadias with/without chordee were evaluated by follow up study in our hospital and private hospital from January 2010 to July 2013. Redo cases, complex hypospadias and proximal hypospadias were excluded. Simple Random sampling technique was followed to the patients were grouped into Group-A (72 patients) and Group-B(72 patients) on the basis of age of the patients. Both Group-A, age between 6 to 18 months and Group-B, more than 18 month to 14 years were operated by Snodgrass procedure. We did follow up 12- 24 months postoperatvely. It can be recommended for repair of anterior and distal penile hypospadias within 6 to 18 months whenever the question of post urethroplasty cosmosis, wound disruption and formation of urethra cutaneous fistula.J Shaheed Suhrawardy Med Coll, December 2015, Vol.7(2); 69-72